2006
DOI: 10.1016/j.fertnstert.2005.07.1320
|View full text |Cite
|
Sign up to set email alerts
|

Preconception sex selection demand and preferences in the United States

Abstract: Objective: Preconception sex selection for nonmedical reasons raises important moral, legal, and social issues. The main concern is based upon the assumption that a widely available service for sex selection will lead to a socially disruptive imbalance of the sexes. For a severe sex ratio distortion to occur, however, at least two conditions have to be met. First, there must be a significant preference for children of a particular sex, and second, there must be a considerable interest in employing sex selectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 26 publications
3
27
1
Order By: Relevance
“…This is in contrast to the data collected from our recent web-based survey of 1,197 men and women aged 18-45 within the United States general population, where only 8% of respondents would use preconception sex selection technology for nonmedical reasons [20]. One possible explanation may be that infertile couples may see their next pregnancy as their last chance to have a child and would therefore like to have an option of choosing the sex.…”
Section: Discussioncontrasting
confidence: 79%
See 1 more Smart Citation
“…This is in contrast to the data collected from our recent web-based survey of 1,197 men and women aged 18-45 within the United States general population, where only 8% of respondents would use preconception sex selection technology for nonmedical reasons [20]. One possible explanation may be that infertile couples may see their next pregnancy as their last chance to have a child and would therefore like to have an option of choosing the sex.…”
Section: Discussioncontrasting
confidence: 79%
“…As recently reported, based on a national survey, the general public in the United States is unlikely to make use of such technologies [20]. Infertile couples, however, may feel differently.…”
Section: Introductionmentioning
confidence: 96%
“…Eight percent said they would use sex selection technology, 74 percent were opposed, and 18 percent were undecided (Dahl, Gupta, Beutel, Stroebel-Richter, Brosig, Tinneberg & Jain 2006). But, looking at data supplied by US fertility clinics, about 42 percent of clinics responding to questions about PGD services provide non-medical sex selection to parents (Baruch, Kaufman & Hudson 2008).…”
Section: Under-the-radar Metaphors In Biopolitical Discoursementioning
confidence: 99%
“…However, there is significant interest in this non-medical application. Dahl found that 8% of respondents would use preconception sex selection services [12] and Jain et al found that 40.8% of women undergoing IVF would select the gender of their child if they could easily do so [13]. In contrast to preconception techniques for gender selection, such as sperm-sorting protocols, the issue of gender selection during cycles of assisted reproduction, and especially so in the absence of infertility or genetic disease, is additionally complicated by cost scale, alloca-tion of limited resources, and ethical considerations regarding the fate of supernumerary embryos, both of the preferred gender and otherwise.…”
Section: Introductionmentioning
confidence: 99%